CORCİ ZEYDAN’IN “İSLAM MEDENİYETİ TARİHİ” ADLI ESERİNE KARŞI YAZILMIŞ BİR TENKİT YAZISI - Mehmet Azimli (İstem, 2005)
This study is criticizing Corci Zeydan’s book, Tarikh al-Tamaddun al-Islami. The critic is Shibli al-Numani from India. Mehmet Akif Ersoy translated it into the Ottoman Turkish Language and it was published in the Review of Sabil al-Rashad. Here, it has been translated into Turkish with some notes